Group B Streptococcus Recto-Vaginal Colonization in Near-Term Pregnant Women, Southwest Ethiopia - Girma, Woubishet (Ethiop J Health Sci, 2020)
BACKGROUND: Group B Streptococcus (GBS) is recognized as an important cause of maternal and neonatal morbidity and mortality. Maternal vaginal carriage of GBS (Streptococcus agalactiae) can lead to vertical transmission to the neonate at the time of delivery. However, little is known about its prevalence, predictors and antibiotic susceptibility pattern in Jimma, Ethiopia. This study assessed the prevalence, antimicrobial susceptibility pattern and determinants of GBS recto-vaginal colonization among near-term pregnant women. METHODS: A cross-sectional study was conducted from May to August 2015 at Jimma University Medical Centre in Southwest Ethiopia. Data through questionnaire and GBS isolates from vaginal and rectal swabs were collected. Antimicrobial susceptibility testing was performed. RESULTS: The overall prevalence of GBS colonization among near term pregnant women (35–37 weeks) was 16.3% (22/135). The majority of GBS isolates were sensitive to Ampicillin and Penicillin G with 95.5% and 90.1%, respectively. Erythromycin and clindamycin were resisted by 50% and 40.9% of the isolates, respectively, whereas gentamicin was resisted by all isolates. GBS colonization was significantly associated with a history of preterm delivery (PTD) (AOR: 6.3, 95% CI: 1.42, 28.3) and history of urinary tract infection (UTI) during current pregnancy (AOR: 6.4, 95% CI, 1.95, 21.1). CONCLUSION: Our study indicated that one among six near-term pregnant women had recto-vaginal GBS colonization. In places where universal screening is not feasible, selective screening for factors particularly history of PTD and UTI during current pregnancy may be a reasonable option. Antibiotic susceptibility testing should be performed while using Erythromycin, Clindamycin or Gentamicin.